ESTIMATION OF PERSONAL DOSE EQUIVALENT HP(0.07) USING CASO4:DY TEFLON DISC-BASED EXTREMITY DOSEMETER. Issue 20 (15th October 2022) - Bhattacharya, Madhumita; Samuel, Kasthuri; Patil, Sandeep; Yadav, Rohit; Bakshi, A K; Singh, Sunil K; Sapra, B K
Abstract: The radiation workers in India use extremity dosemeter in occupational areas where there is likelihood of receiving significant dose to extremities of the body. Algorithm used for the estimation of whole body dose and extremity dose of wrist are same and is based on slab phantom calibration. However, internationally, different phantoms are recommended for calibration of dosemeter used for extremity and whole body. The recommended quantity for estimation of dose to extremity is the personal dose equivalent H p(0.07) at 0.07 mm depth. In light of this, an algorithm was developed for estimation of wrist dose in terms of H p(0.07) based on calibration performed on ISO recommended pillar phantom. Performance of the dosemeter for the estimation of H p(0.07) with new algorithm was carried out at different angular exposures of photon beams and mixed field of photon and beta. Comparison of results obtained for two types of ISO phantoms (slab and pillar) is also performed for photon beams to highlight the uncertainty caused due to the use of the slab phantom. In case of beta radiation, it was found that the size and shape of the phantom has very little influence in the response of the dosemeter. Performance of the dosemeter using ISO slab and ISO pillar phantoms for beta radiation using the prevalent algorithm was carried out and found to be within the uncertainty limits laid down by ISO except at angle 60°.